Pseudo-holomorphic curves: A very quick overview - Oliveira Gonçalo (De Gruyter, 2020)
This is a review article on pseudo-holomorphic curves which attempts at touching all the main analytical results. The goal is to make a user friendly introduction which is accessible to those without an analytical background. Indeed, the major accomplishment of this review is probably its short length.